2022
DOI: 10.1038/s41598-022-15778-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on cancer screening in South Korea

Abstract: The coronavirus disease (COVID-19) pandemic significantly declined cancer screening rates worldwide. Its impact on the South Korean population is unclear, depending on socioeconomic status (SES), residence, and history of chronic disease. This study utilized data (2018–2020) from the Korean National Cancer Screening Survey, an annual cross-sectional study employing nationally representative random sampling. Cancer screening rates were defined as the proportion of the eligible population who received respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…A possible reason for the same screening rate in this survey conducted in 2022 and in previous data may be that students refrained from screening because of the COVID-19 pandemic, which started in 2020. In fact, in South Korea, which has a medical insurance system similar to Japan's, it has been reported that the screening rate of various cancer screenings, including cervical cancer screenings, decreased signi cantly in 2020 compared to that in 2019 [20]. In particular, they described that the screening rate was signi cantly lower among those without chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for the same screening rate in this survey conducted in 2022 and in previous data may be that students refrained from screening because of the COVID-19 pandemic, which started in 2020. In fact, in South Korea, which has a medical insurance system similar to Japan's, it has been reported that the screening rate of various cancer screenings, including cervical cancer screenings, decreased signi cantly in 2020 compared to that in 2019 [20]. In particular, they described that the screening rate was signi cantly lower among those without chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is presumed that the early diagnosis of CRC using colonoscopy increased again within the lag time required to affect stage shifting. The Korean National Cancer Screening Survey, a nationwide, population-based cross-sectional questionnaire survey of about 4,000 respondents every year, reported that the CRC screening rate, using FIT, within the last 1 year among adults aged ≥50 years was 14.8% in 2020, the lowest rate in the past 5 years (2016–2020) [ 9 ]. Another set of data also showed that the participation rate in the Korean national CRC screening program, the NCSP, decreased from 34.8% in 2019 to 25.9% in 2020 and 27.2% in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In April 2020, colonoscopy, colon cancer, and the CRC screening rate in the United States declined by 55.0%, 15.4%, and 37.7%, respectively [ 8 ]. In Korea, a nationwide survey reported that the colorectal cancer screening rate in 2020 decreased by 23% compared to 2019 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many countries around the globe have reported widely on the disruptive impacts of the COVID-19 pandemic on healthcare delivery [9][10][11][12][13][14][15]. At the beginning of the pandemic, many countries suspended or delayed cancer prevention and early diagnostic programmes in addition to many low/medium priority services, such as elective and non-emergency surgeries, outpatient clinics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…palliative or adjuvant chemotherapy), radiotherapy procedures, in-person consultations and supportive care, consequently, leading to the globally reported large-scale reduction in care and service delivery [ 14 , 15 ]. South Korea recorded a significant decline in screening rates for colorectal cancer (−23%), stomach cancer (−17%), breast cancer (−12%) and cervical cancer (−8%) in 2020 in comparison with the preceding year [ 9 ]. Across 41 cancer centres in India, one cohort study showed a 54% reduction in newly registered cancer patients, 46% reduction in patients who had follow-up visits, 37% reduction in outpatient chemotherapy, 49% reduction in major surgeries, 52% reduction in minor surgeries, 23% reduction in patients accessing radiotherapy, 38% reduction in pathological diagnostic tests, 43% reduction in radiological diagnostic tests and 29% reduction in palliative care referrals between March and May 2020 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%